KETERAMPILAN PESERTA DIKLAT TEKNIS SUBSTANTIF PEMBELAJARAN TEMATIK MI DALAM PRAKTIK PEMBELAJARAN DI BALAI DIKLAT KEAGAMAAN SURABAYA - ., Zubaidah (Balai Diklat Keagamaan Surabaya, 2019)
The curriculum functions as the heart of education (curriculum is the heart of education) so that the2017 revised 2013 curriculum characterized by 21st century learning gives greater attention toeducation. The new pattern of education is expected to be able to produce graduates who have characterand are ready to face challenges in the future, but in practice teachers still find it difficult to integratecharacters in learning, so learning still emphasizes substance or teaching material to pursue learningtargets.This study aims to determine the competencies of the participants in the thematic learning training inimplementing learning, while the method used in this study is descriptive qualitative which is preceded bya quantitative approach. The use of these two approaches can be combined in order to produce more perfectconclusions. The results of this study can be described the ability of respondents taken from class 1 andgrade 4 teachers have ”good ” ability in learning practice with a percentage value of 75.7 %Recommended for MI Substantive Technical Learning Training participants in order to further enhancetheir abilities and are expected to add insight by learning the latest 2013 curriculum regulations, especiallyin managing learning.